2023
DOI: 10.1002/eji.201848007
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawn

Abstract: Recently, microRNAs (miRNAs) have been reported to play crucial roles in immune responses and other biological processes, but the role of miR‐181a in myasthenia gravis (MG) has been relatively less studied. We found that miR‐181a was downregulated in the peripheral blood mononuclear cells (PBMCs) of MG patients and was associated with QMGs and anti‐AChR Ab levels. In vitro experiments indicated that miR‐181a was involved in the modulation of CD4+ T cell activation and plasticity and that miR‐181a decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Furthermore, miR-15a expression is reduced in the PBMCs of MG patients and levels are much lower in patients with OMG compared to GMG (98). Yet another miRNA, miR-181a, is downregulated in the PBMCs of MG patients, with a negative correlation between the miR-181a level and QMG score as well as AChR antibody levels (99). Reduced miR-181c expression in the PBMCs of AChR+ MG patients also seems to correlate with elevated serum levels of the interleukins IL-7 and IL-17 (100).…”
Section: Intracellular Mirnas In Mgmentioning
confidence: 97%
“…Furthermore, miR-15a expression is reduced in the PBMCs of MG patients and levels are much lower in patients with OMG compared to GMG (98). Yet another miRNA, miR-181a, is downregulated in the PBMCs of MG patients, with a negative correlation between the miR-181a level and QMG score as well as AChR antibody levels (99). Reduced miR-181c expression in the PBMCs of AChR+ MG patients also seems to correlate with elevated serum levels of the interleukins IL-7 and IL-17 (100).…”
Section: Intracellular Mirnas In Mgmentioning
confidence: 97%
“…For instance, miR-181a targets IL-2 to regulate the activation and differentiation of CD4 + T cells. 25 miR-21 enhances the PLF and MTS of breast cancer cells by targeting LZTFL1. 26 In GC, miRNAs have been found to play various regulatory roles in cell PLF, MGT, multidrug resistance, etc For example, miR-4268 represses the PLF of GC cells by targeting Rab6B 27 ; miR-107 modulates the growth and MGT of GC cells by down-regulating FAT4 to activate PI3K-AKT signaling pathway 28 ; miR-200c reverses the cisplatin resistance of GC by targeting NER-ERCC3/4.…”
Section: Discussionmentioning
confidence: 99%
“…miR-181a is involved in the modulation of CD4+ T-cell activation and associated with the expression of transcription factors related to Th1 and Th17. Liu et al (2019) found that IL-2 is regulated by miR-181a. There is a negative correlation between the levels of miR-181a and IL-2, suggesting that miR-181a is involved in the pathogenesis of MG through the modulation of IL-2 expression (Liu et al, 2019).…”
Section: Mirnas and Mg-related Immune Cells And Cytokinesmentioning
confidence: 99%
“…Liu et al (2019) found that IL-2 is regulated by miR-181a. There is a negative correlation between the levels of miR-181a and IL-2, suggesting that miR-181a is involved in the pathogenesis of MG through the modulation of IL-2 expression (Liu et al, 2019). IL-8 is a chemotactic cytokine that promotes inflammatory cell chemotaxis and induces cell proliferation.…”
Section: Mirnas and Mg-related Immune Cells And Cytokinesmentioning
confidence: 99%